Association between language and early numerical development – The case of quantifiers. Issue 4 (4th July 2022) - Dresen, Verena; Moeller, Korbinian; Pixner, Silvia
ABSTRACT: Language and numerical development are associated in early childhood. In the present study, we focused on the association of the development of children's cardinality understanding of small numbers and their knowledge on unspecific quantifiers (i.e., many, a few). In a longitudinal study, we pursued the research question whether children's knowledge on quantifiers facilitated the acquisition of specific cardinality understanding. Therefore, we followed a total of 76 (34 boys and 42 girls) monolingual German-speaking children aged between 3;6 and 4;6 years at the first measurement time point for two more measurement time points 6 months and one year later. Children's cardinality understanding of small numbers and their quantifier knowledge were assessed using a give-N task. Results indicated a full mediation effect of children's quantifier knowledge at time point 2 on the development of their cardinality understanding from time point 2 to time point 3. This indicates a significant contribution of children's knowledge on unspecific quantifiers to the development of their specific cardinality understanding.